Acute infrarenal abdominal aortic occlusion in a patient with COVID-19 - Rafet Yarımoglu; Saliha Yarımoglu; Hayati Tastan; Halil Ibrahim Erkengel (Annals of Saudi Medicine, 2021)
A high rate of thrombotic complications have been observed in patients infected with COVID-19. These complications are related to increased blood hypercoagulabity, which can cause both venous and arterial thrombosis. We report a case of a 60-year-old man with COVID-19 pneumonia and thrombotic occlusion of the infrarenal abdominal aorta at the time of admission to the hospital. A CT scan showed a crazy-paving pattern in the lungs, consistent with COVID-19. A clinical suspicion of aortic thrombosis was confirmed by CT angiography. Embolectomy was undertaken a few hours later. At the end of the procedure, the patient was taken to the intensive care unit while intubated. The patient then worsened, developing severe renal failure, and died on day 1 after admission to the hospital. A CT scan, which is necessary for diagnosis of COVID-19, and a CT angiography, can be used to diagnose thrombotic events. It should be kept in mind that arterial thrombosis can be present not only in hospitalized COVID-19 patients but also at the time of admission. SIMILAR CASES PUBLSHED: 1